Effectiveness of paraffiscal contributions as an investment strategy in social security (2018)
The objective of this article was to evaluate the effectiveness of parafiscal contributions as an investment strategy for social security. Theoretically it was based on Rodríguez (2012), Villegas (2005), Brito (2011), among others. The type of research was explanatory, non-experimental, transectional, field design. The sample consisted of 25 companies formed by two reporting units, an instrument composed of 45 reagents with a Likert scale was applied. The results determined the recognition of the parties involved on the laws and the low perception of the investment as a reward for the benefit of social security.